2018
DOI: 10.1021/acsami.8b15443
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Nanozymetic Activity of Hybrid Gold Bipyramid–Molybdenum Disulfide Core@Shell Nanostructures for Two-Photon Imaging and Anticancer Therapy

Abstract: In recent years, the concept of combined therapy using gold hybrid nanomaterials has been broadly adopted to pioneer new anticancer treatments. However, their synergistic anticancer effects have yet to be thoroughly investigated. Herein,a hybrid gold nanobipyramid nanostructure coated with molybdenum disulfide (MoS2) semiconductor (AuNBPs@MoS2) was proposed as a smart nanozyme for anticancer therapy and two-photon bioimaging. The hybrid material showed dramatically enhanced localized surface plasmon resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 40 publications
1
54
0
Order By: Relevance
“…Reproduced with permission. [ 29 ] Copyright 2018, American Chemical Society. E) Au nanorods synthesized by seed‐mediated growth.…”
Section: Methods Of Synthesismentioning
confidence: 99%
“…Reproduced with permission. [ 29 ] Copyright 2018, American Chemical Society. E) Au nanorods synthesized by seed‐mediated growth.…”
Section: Methods Of Synthesismentioning
confidence: 99%
“…[94][95][96] Nanomaterials with a photothermal effects are widely used to enhance PTT and have achieved encouraging therapeutic results. 97 Photothermal agents mainly include gold nanomaterials, like GNShs, GNRs, GNCs, GNSs; 39-50 carbon nanomaterials such as SWCNTs, graphene, fullerene, 51-56,98-100 semiconductor nanomaterials such as MoS 2 , WS 2 , Bi 2 Se 3 ; [60][61][62][101][102][103][104] organic NIR dyes such as IGC, IR780, IR820 ( Figure 1B). [63][64][65][66][67][68][69][70][71][72][73][74] However, there are still some ambiguity in PTT.…”
Section: Nanomaterial-based Ptt For Tumor Treatmentmentioning
confidence: 99%
“…Interestingly, recent revisions have shown that hyperthermia can induce dying tumor cells to release antigens, pro-inflammatory cytokines, and immunogenic intracellular substrates, thus promoting immune activation. Nanomaterials with a photothermal effects are widely used to enhance PTT, including gold nanoparticles such as gold nanoshells (GNShs), 39-41 gold nanorods (GNRs), [42][43][44] gold nanocages (GNCs), [45][46][47] gold nanostars (GNSs), 48-50 carbon nanomaterials, such as single-walled carbon nanotubes (SWCNTs), [51][52][53] graphene; [54][55][56] semiconductor nanoparticles, such as copper sulfide (CuS), [57][58][59] molybdenum disulfide (MoS 2 ) [60][61][62] organic NIR dyes such as indocyanine green (IGC), [63][64][65][66][67][68] IR780, 69-71 IR820 [72][73][74] as well as other PTT nanomaterials. In addition to direct killing effect, it is recognized that a key role caused by PTT is immunogenic cell death (ICD).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of strategies have been developed to treat tumor hypoxia and improve the efficacy of PDT 7 , 8 , including hyperbaric oxygen therapy 9 , antitumor angiogenesis therapy 10 , biological reduction therapy 11 , and oxygen transport or generation via nanomaterials 12 , 13 . Recently, an in situ catalytic strategy using nanomaterials to overcome tumor hypoxia has become one of the most promising research directions 14 , 15 , 16 . One in situ catalytic nanomaterial, manganese oxide (MnO 2 ), can decompose to produce oxygen in the acidic environment of the tumor to improve the efficiency of PDT, but the synthesis procedures are complex 17 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%